KOLABORASI LSM DENGAN PEMERINTAH - Suradi Suradi (Politeknik Kesejahteraan Sosial, 2003)
Kajian tentang Pengembangan Kolaborasi LSM dengan Pemerintah dalam Pembangunan Masyarakat (Collaboration between NGO and Government: Studies on Collaboration Development between NGO and Government on Community Development).Non Governmental Organizations and Government sectors have important roles in conductingdevelopment and global life. Both two have certain ability, where government have a lot offund resources and NGO have certain technical skill on conducting development activities. Government and NGO should work together and imposible to neglect each other. Government requires to involve NGO as asked by several donor agencies. Relation pola among Government and NGO within New Order era which cooptative is a good experience. By the relationship, several resources which neglected possible to be actualized in development.Kata kund: kolaborasi, lembaga swadaya masyarakat, relasi